Incontinentia pigmenti in Cajamarca: A case report on infant - Gálvez-Marticorena, Brayan (2015)
Incontinentia pigmenti (IP) or Bloch-Sulzberger syndrome is a rare dominant X-linkeddisease characterized by skinlesions. It may be accompanied by neurological, ophthalmological and dental manifestations. We report the case of a one month and twenty six days old female patient diagnosed with this diseasewho was successfully treated.